Adaptation of functional traits in Gracilaria dura with the local environment: implications for resource management and exploitation - Vieira, Vasco M. N. C. S.; Dawange, Pankaj S.; Jaiswar, Santlal; Sardinha, José P.; Mantri, Vaibhav A. (Frontiers in Marine Science, 2024)
Seaweed functional traits provide insights on natural populations, their adaptations to the local environment, which can be utilized for commercial exploitation. Here, we analyzed the functional traits of Gracilaria dura from two intertidal populations in Veraval and Adri, from the coast of Gujarat, India, over a period of three months. Functional traits were measured by analyzing growth rates, respiration, primary production, antioxidant activity and the content of plant growth hormones. The weight-to-length allometric exponent ≈3 indicated that G. dura grew almost isometrically. Furthermore, frond shape was not significantly different. Fronds in Veraval, resting submerged, grew faster than the fronds in Adri, which, lay exposed in the flat bare rock during low tide. Accordingly, the simultaneous increase in antioxidant activity, O2 production and chlorophyll content in fronds from Adri suggests that stress from desiccation and UV led to the detrimental accumulation of Reactive Oxygen Species, leading to decreased growth and decreased production of growth hormones. The increased Chl-a may indicate enhanced non-photochemical quenching (NPQ) for the dissipation of excess absorbed light. These results aid in establishing the best practices for maximizing biomass yield or the yield of specific molecules. For maximized biomass yield, fronds should not be subject to emersion nor cultivated on the sea-surface. On the other hand, fronds grown subject to emersion or at the sea-surface yield less biomass but more content on molecules such as antioxidants (flavonoids, phenolics, enzymes), that fight stress from desiccation high temperatures and UV. In this case, stress should still be avoided during the initial growth, at the onset of the growth season, in order to not disrupt the production of growth hormones. The increased O2 production at Adri was initially mistakenly perceived as enhanced Net Primary Production. Only a posterior holistic perspective over the whole data allowed to conclude that it was likely the stress-induced detrimental accumulation of Reactive Oxygen Species. More robust experiments are required to establish if the differences observed between locations have led to the evolution of genetic strains specific to each habitat that may show different performances and yields when cultivated in similar environments.